Marketing Library and Information Services: International Perspectives - Gupta, Dinesh K., editor 294341; Koontz, Christie, editor 652057; Massísimo, Àngels, editor 652058; Savard, Réjean, editor 652015; International Federation of Library Associations and Institutions 9987; Gale Group (Online service) 651863 (Munich : K.G. Saur An Imprint of Walter de Gruyter GmbH & Co. KG, 2006)
The marketing of library services is an essential agenda item for almost all kinds of libraries all over the world. In this volume 47 experts from 20 countries address the issue through 40 articles. The bundling of dozens of contributions from a truly international group of librarians, presented in this book, provides a broad spectrum on the topic. This book will thus prove immensely useful, helping both working librarians and future librarians to understand vital issues relating to the marketing of library and information services at the local, national and international level.